Job satisfaction and turnover intention among public sector nurses: Is workload and burnout the issue? - Lenny Dwinijanti; M. F. Arrozi Adhikara; Rokiah Kusumapradja (University of Islam Malang, 2020)
The growing rate of nurse turnover is unavoidable and inevitable. Nursing considered one of the most stressful occupations in the health industry. Unfortunately, there are limited studies published in Indonesia that explain this phenomenon among clinical nurses. This study aims to describe the nurse job satisfaction and turnover intention at public hospitals from workloads and burnout perspective. The design used in this study was quantitative with the survey approach. The data were collected by using simple random sampling from the hospital (cluster B) nurses with the total participant was 190 nurses. The result of this study shows that workload and burnout affect job satisfaction directly. The mediator role of job satisfaction in the effect of workload and burnout on turnover intention is significantly proved. Interestingly, this study failed to prove the effect of workload on turnover intention which means that although many nurses experienced a heavy workload, the majority of nurses in this study feel that the workloads are still reachable or even low due to their young aged. They tend to keep the job since it’s difficult to find any other opportunities. They will intend to leave their job only if they experienced a greater level of burnout and disenchantment.